Implementasi Lean Manufacturing Guna Meminimalisasi Pemborosan Pada Proses Produksi AMDK Jenis Gelas Pada PT.XYZ - Belita Mega Musfita; Nina Aini Mahbubah (Fakultas Teknik, 2021)
As an industrial manufacture , xyz is an enterprise that produces mineral water should take into account in detail the processes in each production line in order to minimize the cost of activities of valueless activities. The impact of these activities is that they are excessive and inadequate to meet customer orders. The research focused on analysing the activities leading to waste to a glass-type production line based on a lean production approach. A case study based explanation is a research approach. According to the current state map, according to the current state map of wasteacross the value stream, the 'ham-filtering' of speakers and the 'cause of process failure on production lines' remains to be determined . Research shows that the dominant waste of the higher sequence is deliberate, the lead time value is 4320 seconds and the cycle time is 60 seconds. Next, the average consumer product of 7.7% exceeds the company's maximum standard. Based on value stream flow map, improvement recommendations as follows: minimize waste, disposal of worthless activities, 5W1H enhancement on the fish edge diagram and preventative maintenance activities to prevent unavoidable defects along production process activities.